2013
DOI: 10.5114/ceji.2013.37747
|View full text |Cite
|
Sign up to set email alerts
|

Possible immunological consequences of filaggrin gene mutation. A case study of a 3-year-old allergic girl

Abstract: Filaggrin is one of the most important structural proteins in the stratum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Finally, the present study is limited by no intestinal microbiota biodiversity information of the studied population. However, a case study report about observed disproportion of skin microbiota in female representative of studied population has been previously published [ 59 ]. Nonetheless, the study provides a strong background for future research devoted to microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the present study is limited by no intestinal microbiota biodiversity information of the studied population. However, a case study report about observed disproportion of skin microbiota in female representative of studied population has been previously published [ 59 ]. Nonetheless, the study provides a strong background for future research devoted to microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of the loss of the water from the epidermis in correlation with the scale of severity of itching could be helpful in demonstrating the phenotypic nature of the filaggrin gene defect [19]. It seems important to extend the study by adding the data on the course of the disorder in the first years of the patient's disease with mutations in the filaggrin gene defect life [20].…”
Section: Discussionmentioning
confidence: 99%